2022
DOI: 10.1186/s12884-022-04479-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Canadian mothers’ anger during the postpartum period: a cross-sectional survey

Abstract: Background Although some women experience anger as a mood problem after childbirth, postpartum anger has been neglected by researchers. Mothers’ and infants’ poor sleep quality during the postpartum period has been associated with mothers’ depressive symptoms; however, links between mothers’ sleep quality and postpartum anger are unclear. This study aimed to determine proportions of women with intense anger, depressive symptoms, and comorbid intense anger and depressive symptoms, and to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Various constructs have been assessed by study authors in relation to the topic of maternal mental health. These include commonly investigated experiences such as depression, anxiety, 'stress' [4] and 'distress' [5,6] as well as less commonly reported 'wellbeing' [7][8][9], 'emotional disorders' [10], symptoms of PTSD (Post Traumatic Stress Disorder) [11][12][13], suicidal ideation [14], mood instability [15], anger [16] and intolerance of uncertainty [17]. These experiences have been differentiated with regard to the 'antenatal' and 'postnatal' time periods, or both [18].…”
Section: Issues Of Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various constructs have been assessed by study authors in relation to the topic of maternal mental health. These include commonly investigated experiences such as depression, anxiety, 'stress' [4] and 'distress' [5,6] as well as less commonly reported 'wellbeing' [7][8][9], 'emotional disorders' [10], symptoms of PTSD (Post Traumatic Stress Disorder) [11][12][13], suicidal ideation [14], mood instability [15], anger [16] and intolerance of uncertainty [17]. These experiences have been differentiated with regard to the 'antenatal' and 'postnatal' time periods, or both [18].…”
Section: Issues Of Definitionmentioning
confidence: 99%
“…A mental health related measure needs to be well developed and thoroughly validated, with clear definition and scope, to ensure clarity of findings, meaningful interpretation and reproducibility. This Collection includes large and small scale studies, cross-sectional studies [5,16,11], cohort studies [18,22] and studies validating new screening or measurement tools [8,13,17].…”
Section: Rationale For This Collectionmentioning
confidence: 99%
“…However, Ou et al (2022) found that, of a sample of women in the postpartum period who experienced intense anger, half experienced probable depression while half did not, suggesting that anger is a distinct mood problem that can be independent of depressive symptoms. Regression analysis indicated that income, number of children, depressive symptoms, maternal sleep quality, and maternal anger about infant sleep were significant predictors of intense maternal anger ( Ou et al, 2022 ). Empirical sources provide limited exploration of mothers’ characterization of anger.…”
Section: Introductionmentioning
confidence: 97%
“…For example, in a meta-ethnographic synthesis of PND in women migrating from low-income to higher income countries, anger was prominently represented as "I am worried, alone, and angry-this is not me" amongst four main themes including making sense of feelings, dealing with feelings, and actively changing how women felt about their situation (Schmied et al, 2011). However, Ou et al (2022) found that, of a sample of women in the postpartum period who experienced intense anger, half experienced probable depression while half did not, suggesting that anger is a distinct mood problem that can be independent of depressive symptoms. Regression analysis indicated that income, number of children, depressive symptoms, maternal sleep quality, and maternal anger about infant sleep were significant predictors of intense maternal anger (Ou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…[3] On the other hand, most adolescents have a moderate level of anger, and 41% of the adolescents express their anger by shouting and fighting. [4] Symptoms related to anger and aggression have been reported and include increased anger in premenstrual women, [5,6] postpartum women, [7] menopausal women, [8] and other psychiatric outpatients. [9][10][11] Anger and aggression are personality traits associated with suicide attempts, a major risk factor for suicide commission.…”
Section: Introductionmentioning
confidence: 99%